Phase II study of ipilimumab and nivolumab in leptomeningeal carcinomatosis - Priscilla K. Brastianos; Matthew R. Strickland; Eudocia Quant Lee; Nancy Wang; Justine V. Cohen; Ugonma Chukwueke; Deborah Anne Forst; April Eichler; Beth Overmoyer; Nancy U. Lin; Wendy Y. Chen; Aditya Bardia; et al. (Nature Communications, 2021)
Leptomeningeal metastases from solid tumors are a rare complication with a very poor prognosis. Here the authors report the efficacy and safety of combined ipilimumab and nivolumab in patients with leptomeningeal carcinomatosis.